Exploring Purchasing Determinants for a Low Fat Content Salami: Are Consumers Willing to Pay for an Additional Premium? - Di Vita, Giuseppe; Zanchini, Raffaele; Spina, Daniela; Maesano, Giulia; La Via, Giovanni; D'Amico, Mario (Frontiers in Sustainable Food Systems, 2022)
Consumers today are increasingly moving toward healthier lifestyles and food purchasing habits. This new awareness has also prompted the meat industry, usually indicted for the use of harmful compounds and ingredients such as additives, salt, and fat, to introduce innovative measures to meet demand. This study aims to assess consumer willingness to pay an additional price premium (APP) for a healthy salami by identifying which factors are more likely to have an effect on the willingness to purchase, such as socio-demographic and product and market-related attributes. An Ordered Logit model has been applied to define factors influencing consumers' willingness to pay for a low-fat salami. Results show a favorable consumer acceptance of reduced-fat salami conveyed by the willingness of consumers to pay an additional price for this product and confirm that the health awareness of consumers is an important driving force in cured meat marketing strategies.